Peningkatan Pengetahuan Siswa SMKN 1 Nguling dalam Memanfaatkan Daun Kenikir dan Seledri sebagai Bahan Baku Minuman Herbal - Sri Winarsih; Warkoyo; Sukardi; Hanifah Nada Rifa; Hanifa Dhiya Ulhaq (Politeknik Piksi Ganesha Indonesia, 2025)
Many health problems were caused by the formation of free radicals in the body, so antioxidants are needed from various food plant sources that contain phytopharmacia. Various food plants that can be used as herbs are abundant in the surrounding environment, but due to limited knowledge, plants that have many health benefits have not been maximally utilized. Therefore, socialization and training are given to teachers and students with the hope that the knowledge gained will be spread more widely to the community. The methods used were discussion and practice. lecture was the method used to convey material about various herbal plants and their benefits. A demonstration practice of making herbal drinks was used to improve the skills of the students. Evaluation of the activity was carried out by pre-test and post-test. The socialization activities have produced herbal drinks. Herbal drinks can be accepted by teachers and students through organoleptic tests. A hedonic scale is used to assess the level of preference for herbal drinks. 18.2% of panelists liked the herbal drink, 9.1% of panelists liked it slightly, and 72.7% were neither like nor dislike (neutral). The knowledge of the students has increased after being given an explanation of the material, as evidenced by the results of the t test on the pre-test and post-test scores, which are significant